Reflection in pre-service teacher education: exploring the nature of four EFL pre-service teachers' reflections. Issue 1 (2nd January 2019) - Yalcin Arslan, Fadime
ABSTRACT: This year-long study examined the nature of reflections belonging to four EFL (English as a Foreign Language) pre-service teachers. It was longitudinal in nature, taking place during the phases of teachers' initial observation, teaching practice, and entry into the teaching profession. This study aimed to investigate the nature of student-teachers' individual reflections throughout the phases of school experience, teaching practice, and entry into the workplace. Data collection was facilitated via interviews conducted throughout the study's duration, and the collected data were subsequently analyzed deductively using content analysis. In addition, the onion model of reflection of was employed for interpretation of the data. The findings of this interpretation indicated that although most of the reflections concerned environment, behavior, and competence (outer level of the onion model), some of the reflections nevertheless pertained to mission (inner level of the onion model). Moreover, an examination of participants' individual reflection processes revealed that although reflections initially were outer-level in nature, by the end of the study they had become more inner-level-oriented.